'Measure Twice, Cut Once'—Revisiting the Strength and Impact of Local Planning Regulation of Housing Development in England. (October 2014) - Bramley, Glen; Watkins, David
There has been growing interest in the impact of land-use regulation and planning on housing development and markets, and a consequent search for quantified measures of their extent and efficacy. Nevertheless, despite the UK having a long-established and comprehensive planning system, this kind of quantitative analysis of system performance has been limited. This paper assembles and reports on a set of local-level measures for England for the late 2000s and assesses their effectiveness in predicting the key flow-of-consents measure and actual housing development. The pattern of restrictiveness is assessed against broad sustainability criteria including urban settlement structure, economic growth potential, and housing affordability and need. We also assess recent changes and the potential impact of a major system change towards more localised planning decision making.